Meigs Syndrome and Elevated CA-125: Case Report and Literature Review of an Unusual Presentation Mimicking Ovarian Cancer - Irene Iavarone; Michela Padovano; Francesca Pasanisi; Luigi Della Corte; Elvira La Mantia; Carlo Ronsini (Medicina, 2023)
Background and Objectives: Meigs syndrome is represented by a benign adnexal tumor, ascites, and hydrothorax. Even though the ovarian mass is often characterized by a fibroma-like origin, cancer antigen-125 (CA-125) serum levels could be elevated as in the development of ovarian cancer. Here, we present the case of a patient with Meigs syndrome and increased CA-125. Materials and Methods: We performed systematic research for articles including similar cases in PubMed, EMBASE, and Scopus in February 2023, adopting the string of idioms: “Meigs syndrome AND Cancer antigen 125”, and following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results: Eligible records were 25. Hydrothorax was right-sided in 10 cases over 25; left-sided in two patients over 25. Concerning ascites, two patients showed more than 6 L of ascitic fluid, whereas three patients had 6 L or less. CA-125 elevation ranged from 149 IU/mL to 3803 IU/mL. Adnexal mass histotypes were: struma ovarii (12 cases), thecomas (two cases), fibrothecomas (five cases), fibromas (five cases), and one sclerosing stromal tumor (SST). Conclusions: In postmenopausal women with elevated CA-125 serum levels and an adnexal mass suspicious for malignancy at ultrasound (US), ascites and pleural effusion, surgery, and histopathological examination are necessary. MS is a diagnostic option, with an excellent prognosis after exeresis of the mass.